2009
DOI: 10.1007/s00421-009-1250-z
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training improves femoral artery endothelial dysfunction in aged rats

Abstract: Although endurance exercise improves age-associated endothelial dysfunction, few studies have examined the effects of resistance training and the potential molecular mechanisms involved in altering vascular reactivity with age. Young (9 months) and aged (20 months) male, Fisher 344 rats were divided into four groups: Young Sedentary (YS, n = 14), Young Trained (YT, n = 10), Aged Sedentary (AS, n = 12), and Aged Trained (AT, n = 10). Resistance training consisted of climbing a 1 m wire ladder, at an 85 degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
0
25
0
2
Order By: Relevance
“…27,28 A recent prospective study of 1429 participants with physician-diagnosed CVD showed that participation in moderate-tovigorous physical activity at least three times per week was associated with a reduced risk of CVD death. 34,35 Finally, the tendency for the aggregation of various risk factors was expected, but it was also expected that both exercise programs would contradict this tendency. 2 Available research focusing on moderate-to-vigorous exercise reported a direct protective effect on vascular factors, and improvements in BP, lipid profile and body fat loss.…”
Section: Discussionmentioning
confidence: 97%
“…27,28 A recent prospective study of 1429 participants with physician-diagnosed CVD showed that participation in moderate-tovigorous physical activity at least three times per week was associated with a reduced risk of CVD death. 34,35 Finally, the tendency for the aggregation of various risk factors was expected, but it was also expected that both exercise programs would contradict this tendency. 2 Available research focusing on moderate-to-vigorous exercise reported a direct protective effect on vascular factors, and improvements in BP, lipid profile and body fat loss.…”
Section: Discussionmentioning
confidence: 97%
“…Exercise is a potent stimulus for induction of Hsp and increases localization of Hsp in the coronary and skeletal muscle vasculature [6768], and this is thought to contribute to the protective effects of aerobic exercise in these tissues [6769]. Although few studies have specifically examined the effects of aerobic exercise on Hsp induction in the systemic vasculature, resistance training-induced increases in femoral artery Hsp90 were associated with improve-ments in eNOS activity and arterial function in young and old rats [70]. In the present study, we observed that arterial expression of Hsp90 was significantly increased in both young and old mice following the voluntary aerobic exercise intervention.…”
Section: Discussionmentioning
confidence: 99%
“…If all eight climbs were successfully completed, an extra 40 g were added to the 9th climb ‐setting a new maximal load. Each animal performed 8‐12 dynamic movements/repetitions per climb …”
Section: Methodsmentioning
confidence: 99%
“…BDL-rats tolerated progressive resistance training and as a result muscle strength and calf size were greater in BDL-exercise rats compared to BDL-controls (not exercising) at the end of the study.successfully completed, an extra 40 g were added to the 9th climb -setting a new maximal load. Each animal performed 8-12 dynamic movements/repetitions per climb 17.…”
mentioning
confidence: 99%